Penanganan Kesehatan Jiwa pada Korban Bencana - Miswarti Miswarti; Maidawilis Maidawilis; Jufrika Gusni; Rosmi Eni; Hasmita Hasmita (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
: Disaster is an event or series of events that threatens and disrupts people's lives and livelihoods caused both by natural factors and/or non-natural factors as well as human factors resulting in human casualties, environmental damage, loss of property and psychological impacts (Law No. 24 , 2007). The psychological impact is affected by the occurrence of disasters in various regions in Indonesia, ranging from natural, artificial, to social disasters which claim many victims. The victims of the disaster needed help, and not only physical medical assistance but also mental health support. So that this will cause material losses, the victims of natural disasters will also be overcome by deep sadness due to the loss of family or relatives, shock, to trauma which can lead to mental disorders. Efforts made to deal with post-disaster trauma are physical treatment and support in the form of mentoring from community. A week to four weeks later, Community need to carry out environmental monitoring and evaluation and other threats. Based on the above problems, it is necessary to have community service to be able to cooperate between various parties in preparing for the mental health treatment of disaster victims. The purpose of the service is for community to understand the handling of mental health for disaster victims. The service will be held in May 2023. The service participants are the community. The results of the dedication showed that more than 80% of the participants were able to know how to deal with the mental health of disaster victims..